Agro-economic analysis of sustainable cropping patterns in hydric rice fallows of upper Brahmaputra valley, Asom - DHARAM SINGH; B P BHASKAR; U BARUAH; DIPAK SARKAR (The Indian Journal of Agricultural Sciences, 2014)
Three post rainy season crops, viz. potato (Solanum tuberosum L.), pea (Pisum sativum L.) and mustard (Brassica juncea L.) were evaluated for their economic efficiency for two years (2005-06 to 2006-07) in four hydric rice growing soils under two management levels (farmers' practice and recommended package of practices) in upper Brahmaputra valley of Asom. The farm experimental results recorded tuber yield of 208 q/ha for potato, 9.48 q/ha of grain yield of mustard and 57.5 q/ha of green pod yield of peas under recommended doses with high benefit cost ratio of 2.44 for potato and 2.35 for mustard in Lahangaon series (coarse loamy Aeric Fluvaquents) as compared to farmer’s practice (benefit cost ratio of 1.57 for potato to 1.71 for peas). The performance of potato and peas in rice fallows of Brahmaputra valley was evident in all soils under recommended practices in terms of benefit cost ratio, efficient uptake of NPK and yield.